Modeling the development of vocational competence : a psychometric model for economic domains - Klotz, Viola Katharina [Verfasser]; Winther, Esther [Verfasser]; Festner, Dagmar [Verfasser] (My University, 2015)
"This article discusses the development of vocational competence through economic vocational educational training (VET) from a theoretical and psychometric perspective. Most assessment and competence models tend to adopt a state perspective toward assessments of competence and carve out different structures of competence for diverse vocational domains. However, the order and at what stages of development these identified structures actually occur remains uncertain. This study therefore moves beyond a static perspective to denote changes in competence over the duration of vocational training, using item response theory-based scaling and a cross-sectional database of 877 economic apprentices. The resulting four-stage psychometric model represents a systematization of the development of vocational competence, characterized by the degree of occupational specificity and different forms of cognitive processing. This proposed psychometric model can be used to inform educational researchers and practitioners about the different stages of competence development, such that they can both assess and teach economic competence more effectively." (Authors' abstract, BIBB-Doku)
Keywords: L 3 Lehr-Lern-Forschung; L 6.3.1 Diagnose- & Messinstrumente; S 6.4.1 Kaufleute; T 4.2 Psychologie; Kompetenzforschung; Kompetenzdiagnostik; Kompetenzentwicklung; Kompetenzfeststellung; Lernerfolgskontrolle; Kompetenzmodell; Kaufmännischer Beruf; Psychometrie; Testtheorie; Psychologische Theorie